Combination of Corticosteroid with Local Anesthesia Injection and Hydrodissection for a case of Tennis Elbow and Radial Tunnel Syndrome. - Sangroula, Rakshya; Das, Gautam; Sukhupayo, Rojina; Shakya , Eva (Birat Journal of Health Sciences, 2024)
Tennis elbow, or lateral epicondylitis, is a common condition characterized by pain and tenderness over the lateral aspect of the elbow. Radial tunnel syndrome, often presenting with similar symptoms, is a less recognized but potentially concomitant pathology. We present a case report of a 44 years old male presenting with symptoms consistent with both tennis elbow and radial tunnel syndrome. The patient underwent a thorough assessment, including clinical examination and diagnostic imaging, confirming the dual pathology. He was then managed with a combined approach (corticosteroids and local anesthetics) injection along with fenestration of common extensor tendonto address the tennis elbow, followed by hydrodissection of the radial tunnel with 5% dextrose to relieve compression on the radial nerve. The patient experienced significant improvement in pain and functional outcomes at follow-up appointments. This case underlines the importance of recognizing and treating both tennis elbow and radial tunnel syndrome concurrently for optimal patient outcomes. As this is a single case study more studies are needed to further clarify the effectiveness and long-term benefits of this combined therapeutic approach.